Colletotrichum clavatum sp. nov. identified as the causal agent of olive anthracnose in Italy - FAEDDA, Roberto; AGOSTEO, Giovanni Enrico; SCHENA, Leonardo; MOSCA, Saveria; FRISULLO, Salvatore; MAGNANO DI SAN LIO, Gaetano; CACCIOLA, Santa Olga (Phytopathologia Mediterranea, 2011)
Molecular analyses of a large population of isolates, previously identified as group B or genetic group A4 of the Colletotrichum acutatum species complex, mainly of Italian origin from olive, but also from other hosts collected since 1992, confirmed a well-resolved phylogenetic lineage with distinctive phenotypic characters which can be recognized as a separate species. Based on RAPD genomic fingerprinting, ITS and β-tubulin DNA sequences, this species was clearly distinct from C. acutatum sensu stricto, C. fioriniae and C. simmondsii as well as from the genetic groups A1, A6, A7 and A8, all previously referred to as C. acutatum sensu lato. Group A4 is widespread in Europe, being responsible for olive anthracnose epidemics in some Mediterranean countries, including Greece, Italy, Montenegro, Portugal and Spain; moreover, it causes anthracnose diseases on a wide range of other hosts including about 20 different genera of woody and herbaceous plants, ornamentals and fruit trees. This new anamorphic taxon is described as Colletotrichum clavatum sp. nov.